Predicate Induction and Visual Analaytics: Bridging Human and Automated Reasoning - Montambault, Brian (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026.; Submitted to the Dept. of Computer Science.; Advisor: Remco Chang.; Committee: Robert Jacob, Elaine Short, Jonathan Lamontagne, and Jeff Gilbert.; Keyword: Computer science